Inflammatory markers mediated diabetic nephropathy in patients with type 1 and type 2 diabetes mellitus - Sheet Saleh, Madha M.; Dhamad, Ghuroob D.; Kamel, Laith Abul-Ellah (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Diabetic nephropathy (DN) represents the most common cause of end stage renal disease (ESRD) worldwide. Diabetic nephropathy occurs as a result of an interaction between hemodynamic and metabolic factors, however recent evidence shows an increase growing support for the notion that inflammation plays a key role in the pathogenesis of diabetic nephropathy.Objectives: To speculate the role of IL-18 and TNF-α proinflammatory cytokines in the initiation and development of diabetic nephropathy in T1DM and T2DM.Materials and methods: Eighty seven T1DM and T2DM patients with or without DN were enrolled. IL-18 and TNF-α cytokines were measured by solid phase immunosorbent assays.Materials and methods: Eighty seven T1DM and T2DM patients with or without DN were enrolled. IL-18 and TNF-α cytokines were measured by solid phase immunosorbent assays.Results: IL-18 had increased significantly in patients with DN compared to those without DN in T1DM and T2DM patients whereas TNF-α had exhibited a significant elevation among patients with DN compared to those without DN in T2DM but not T1DM.Conclusion: IL-18 is suggested to play a crucial role in the initiation, development, and progression of DN in T1DM and T2DM patients whereas TNF-α is playing a similar role but only in T1DM patients with DN.